(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Remarks about Phtheochroa fulvicinctana (Constant, 1893), Cydia vallesiaca (Sauter, 1968) and Dichrorampha consortana (Stephens, 1852) collected in Italy are reported. Ph. fulvicinctana and C. vallesiaca are new for the ltalian fauna, the presence of D. consortana in Italy is confirmed.